Association between childhood sexual abuse and early sexual debut among Chinese adolescents: The role of sexual and reproductive health education - Wen, Xu; Ding, Ruoxi; Guo, Chao; Zheng, Xiaoying (Frontiers in Reproductive Health, 2023)
Background Despite accumulating evidence of the long-term impacts of childhood sexual abuse (CSA), few studies have investigated the association between CSA and early sexual debut among adolescents. In this study, we examine the relationship between CSA and early initiation of sexual intercourse among Chinese youth, and the role of school-based sex education in this association, based on a nationally representative survey. Methods Data were collected from the Survey of Youth Access to Reproductive Health in China (YARHC) conducted in 2009. Multivariable logistic regression models were used to investigate the association between CSA experience and early sexual debut, and the interaction terms between sexual and reproductive health education and CSA were included to examine the role of education in the association between CSA and early sexual debut. Results Among 4,907 sexually experienced youth, 1,062 (21.6%) made their early sexual debut. After adjusting for sociodemographic characteristics, it was found that CSA experience was significantly associated with early sexual debut, with an adjusted odds ratio of 3.13 (95% CI: 1.67–5.87). Receiving any type of sexuality education (reproductive health, sexually transmitted disease (STD) and HIV prevention, or contraception use) was not associated with a decreased risk of early sexual debut. Conclusion Our results indicate a greater risk of early sexual debut among Chinese adolescents with a history of CSA, and only 46.7% sexually experienced youth had received prior sex education, which suggested an inadequacy of school-based sexuality education. To reduce this risk, targeted intervention with timely and adequate sexuality education for both early starters of sexual intercourse and CSA victims is warranted in China.